Thermal-tolerant potential of ordinary Chlorella pyrenoidosa and the promotion of cell harvesting by heterotrophic cultivation at high temperature - Dai, Yu-Ren; Wang, Die; Zhu, Yu-Rong; Yang, Kun-Xiao; Jiao, Ning; Sun, Zhong-Liang; Wang, Shi-Kai (Frontiers in Bioengineering and Biotechnology, 2022)
During heterotrophic cultivation of microalgae, a cooled process against temperature rise caused by the metabolism of exogenous organic carbon sources greatly increases cultivation cost. Furthermore, microalgae harvesting is also a cost-consumption process. Cell harvesting efficiency is closely related with the characteristics of algal cells. It may be possible to change cell characteristics through controlling culture conditions to make it easier to be harvested. In this study, the mesophilic Chlorella pyrenoidosa was found as a thermal tolerant species under heterotrophic mode. The cells could maintain their maximal specific growth rate at 40°C and reached 1.45 day-1, which was equivalent to that of cultures at 35°C but significantly higher than that cultured at lower temperatures. Interestingly, the cells cultured at 40°C were much easier to be harvested than that of cells at lower temperatures. The harvesting efficiency of cells cultured at 40°C reached 96.83% after sedimentation for 240 min while cells cultured at lower temperatures were reluctant to settle. Likely, same circumstance occurred when cell harvested by centrifugation or flocculation. The promotion of cell harvesting for cells cultured at high temperature was mainly attributed to the increased cell size and decreased cell surface charge. To the best of our knowledge, this is the first report that cultured at high temperature can promote microalgae harvesting. This study explored a new approach to simplify the cultivation and harvesting of microalgae, which effectively reduces the microalgae production